ANALYSIS EDUCATIONAL PROGRAMS AND MODELS OF ECONOMIC TRAINING IN UKRAINE - Zagorodnya, Alla A. (Educological discourse, 2016)
The author analyzes the curricula and training specialists models economic sector in Ukraine. Notes that Ukraine recognizing the principles on which the European educational, research and cultural space and pledging to reform the national education system according to the main provisions of the Bologna Declaration, among which the most important quality of higher education is considered first of all necessary to improve regulatory support of higher education institutions (HEIs), including the educational process. The main regulatory document defining the organization of educational process in a specific area of education or professional training is the curriculum. Hence, the need to modernize curricula for bachelors and masters.